Comparative Analysis of METRIC Model and Atmometer Methods for Estimating Actual Evapotranspiration. (3rd December 2017) - Reyes-González, Arturo; Kjaersgaard, Jeppe; Trooien, Todd; Hay, Christopher; Ahiablame, Laurent
Abstract : Accurate estimation of crop evapotranspiration (ET) is a key factor in agricultural water management including irrigated agriculture. The objective of this study was to compare ET estimated from the satellite-based remote sensing METRIC model to in situ atmometer readings. Atmometer readings were recorded from three sites in eastern South Dakota every morning between 8:15 and 8:30 AM for the duration of the 2016 growing season. Seven corresponding clear sky images from Landsat 7 and Landsat 8 (Path 29, Row 29) were processed and used for comparison. Three corn fields in three sites were used to compare actual evapotranspiration (ET a ). The results showed a good relationship between ET a estimated by the METRIC model (ET a -METRIC) and ET a estimated with atmometer (ET a -atm) (r 2 = 0.87, index of agreement of 0.84, and RMSE = 0.65 mm day −1 ). However, ET a -atm values were consistently lower than ET a -METRIC values. The differences in daily ET a between the two methods increase with high wind speed values (>4 m s −1 ). Results from this study are useful for improving irrigation water management at local and field scales.